Consciences bound and liberated. Issue 2 (20th May 2019) - Hopgood, Miles
Abstract: A hallmark of Martin Luther's theology was his persistent concern for the individual's conscience before God. Nowhere were these concerns felt more deeply than in Luther's understanding of church reform, where he sought to introduce change in a way that did not introduce doubt or impede faith. Among Lutherans in North America, respect for conscience has found a second home in how early Lutherans attempted to establish an American identity for themselves and reconsider their ecumenical relations. After briefly outlining Luther's use of the appeal to conscience, this paper looks at its use in early North American Lutheranism in the thought of Samuel Simon Schmucker before finally considering its use in the twenty‐first century.